Cost Management Guidelines for Decision Making and Control - Thawanratphokin, Theerawat; Changkomchome, Thanawan; Sensang, Phongamphai (Journal of Humanities and Social Sciences Thonburi University, 2024)
This academic article has the objective of providing cost management guidelines for decision-making and control. in administration and organization management to be efficient and effective using management accounting tools and concepts and cost accounting in the current situation of intense trade competition. As a result, most businesses must adjust their production and management structures and formats. Be flexible according to the competitive conditions of the market. This giving rise to the concept of modern cost management. By developing new principles and strategic cost management. So that executives are aware of the strengths and weaknesses of their work. Including seeing the opportunity to make a profit. and various obstacles that may affect the business in the future. The concept of cost management consists of 1) the concept of activity costs, 2) the concept of allocation of expenses, 3) the concept of standard costs, 4) the concept of inventories, 5) the concept of fair value, and 6) Budget management concepts Together with the concepts of decision making and control, it consists of 1) organizational structure management, 2) business process management, 3) use of technology and equipment, 4) warehouse management, 5) financial policy management, and 6) planning and control. Project